Direct Evidence of the Presence of Hybrid Charge Transfer State in a Perovskite Nanocrystal‐Polythiophene Blend Solid State Film - Tersilla Virgili; Mariacecilia Pasini; Michele Guizzardi; Edoardo Mosconi; Stefania Milanese; Luca Gregori; Asma A. Alothman; Maria Luisa De Giorgi; Arianna Creti; Maryna Bodnarchuk; Mauro Lomascolo; Marco Anni (Advanced Materials Interfaces)
Abstract In this paper, the photophysical properties of a hybrid material, composed of a conjugated polymer and perovskite nanocrystals, are investigated by ultrafast spectroscopy and morphological characterization. The relaxation dynamics of a drop‐casted film from the semiconducting polythiophene (P3HT) and a green‐emitting CsPbBr3 (zwitterionic sulfobetaine ‐capped) perovskite nanocrystals (NCs) solution is studied. The transient spectroscopy presents a very long photobleaching signal peaked at 516 nm not present in the single components of the blend. The scanning electron and confocal fluorescence microscopy images show that the P3HT and the CsPbBr3 NCs are finely mixed in the film. The presence of a very efficient hole transfer from the nanocrystal to the polymeric chain that induces the formation of a long ‐lived charge‐transfer state as shown in the pump‐probe measurements is proposed. The theoretical model reveals the important role of the zwitterionic sulfobetaine capper in this process. The perovskite strongly adsorbs the surfactant, while the polythiophene chain is not directly bound to the perovskite. Instead, it interacts with the surfactant itself, contributing to the electronic properties of the overall system.